Enhancing Childrens Cognitive Abilities Through â€œJelajah Alamâ€ Apllication : Promoting Well-being - Lely Ika Mariyati; Zaki Nur Fahmawati; Uce Indahyanti; Berlian Putri Pertiwi; Rolando Jordan Permana Putra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The use of technology in the early childhood learning process is rarely found despite the numerous benefits it offers. This study aimed to examine the effectiveness of the